Fenomena Mengunggah Film Pendek di Media Sosial pada Mahasiswa Komunikasi Universitas Islam Riau - Caniago, Alfi; Hero, Eko (Riauan Consulting and Communication, 2022)
Social media has a big role in the functional and operational communicate or publish information to the public or the audience is in the virtual world of the lives of those who are positive and some are negative for the wider community. Social media communication functions by interacting through the Internet. To up to student creativity at this time there is a container that is large enough that social media, because the social media we can do anything like upload, comment, video streaming and direct messages. The purpose of this study was to determine the phenomenon of short films uploaded to social media and interest upload short films to social media. The theory used in this research is the theory of symbolic interaction. Symbolic Interaction placing human communication in a central position and understand human behavior. The subjects used in this study were students of the faculty of science communication service branch, 2013. The data collection technique was interview with university students of communication science class, 2013, observation, and documentation. Upload very widespread phenomena and helped with the advances in technology are increasingly sophisticated, and the average at this time people have accounts on social media. Especially teenagers are very interested in social media, because in there they can publish their creative ideas and to be quickly seen by many people.